FRI0182 RISK FACTORS ASSOCIATED WITH RENAL INVOLVEMENT IN PRIMARY SJÖGREN'S SYNDROME: DATA FROM THE SPANISH SJÖGRENSER COHORT. (2nd June 2020) - Narváez, J.; Sánchez-Piedra, C.; Fernandez Castro, M.; Martinez Taboada, V.; Olive, A.; Rosas, J.; García-Vadillo, A.; Judez, E.; Ruiz Lucea, E.; Romani, L.; Andreu, J. L.
Abstract : Objectives: To investigate the prevalence, risk factors, and effects of primary renal disease on morbidity and mortality in patients with primary Sjögren's syndrome (pSS). Methods: All patients in the SJÖGRENSER (registry of adult SSp patients of the Spanish Society of Rheumatology, cross-sectional phase) cohort were retrospectively investigated for the presence of clinically significant renal involvement directly related to pSS activity. Results: Of the 437 patients investigated, 39 (9%) presented overt renal involvement during follow-up. Severe renal disease necessitating kidney biopsy was relatively rare (23%). Renal involvement may complicate pSS at any time during the disease course and is associated with severe disease (indicated by higher scores of involvement, activity, and damage), systemic multiorgan involvement, and a higher frequency of lymphoma. Multivariate analysis showed that older age (odds ratio [OR] 1.03, 95% confidence interval [CI] 1.00–1.07), higher European League Against Rheumatism Sjogren's Syndrome Disease Activity Index scores (OR 1.1, CI 1.03–1.18), serum anti-La/SSB positivity (OR 6.44, CI 1.36–30.37), and non-vasculitic cutaneous involvement (OR 8.64, 1.33–55.90) were independently associated with this complication. Chronic renal failure developed in 23 of 39 patients (59%); only 1 of them progressed to end-stage renal disease necessitating renal replacement therapy. Patients with renal disease showed higher Sjögren's syndrome disease damage index scores (SSDDI), higher rates of hospitalization due to disease activity and higher rates of clinically relevant comorbidities. Conclusion: Renal involvement is an uncommon complication in pSS that was observed in 9% of patients. Although categorized as a non-negligible comorbidity, this condition shows a favorable prognosis. Disclosure of Interests: None declared